In situ surface-enhanced Raman spectroscopy to investigate polyyne formation during pulsed laser ablation in liquid. (15th April 2022) - Marabotti, P.; Peggiani, S.; Facibeni, A.; Serafini, P.; Milani, A.; Russo, V.; Li Bassi, A.; Casari, C.S.
Abstract: The synthesis of polyynes during their formation by pulsed laser ablation in liquid (i.e., acetonitrile) has been analyzed by in situ surface-enhanced Raman spectroscopy (SERS). A polyethylene pellet, functionalized with silver nanoparticles and placed into the ablation medium, served as SERS active surface. This innovative approach granted the possibility to investigate the dynamics of formation and degradation of polyynes with a time-resolution of a few seconds, starting from the early stages of ablation when the concentration is low. The processes occurring during the synthesis have been studied comparing the in situ SERS signal of polyynes and byproducts in the solution. The different kinetics of short and long polyynes have been investigated by their in situ SERS signal, exploring the final distribution of chain lengths. Ex situ UV–Vis and high-performance liquid chromatography confirmed the observations gained from in situ SERS data and validated this innovative in situ and in operando analysis. Graphical abstract: Image 1